Development of surface plasmon resonance sensor for determining zinc ion using novel active nanolayers as probe - Yap, Wing Fen; Mat Yunus, Wan Mahmood; Talib, Zainal Abidin; Yusof, Nor Azah (Elsevier, 2015)
In this study, novel active nanolayers in combination with surface plasmon resonance (SPR) system for zinc ion (Zn2+) detection has been developed. The gold surface used for the SPR system was modified with the novel developed active nanolayers, i.e. chitosan and chitosan–tetrabutyl thiuram disulfide (chitosan–TBTDS). Both chitosan and chitosan–TBTDS active layers were fabricated on the gold surface by spin coating technique. The system was used to monitor SPR signal for Zn2+ in aqueous media with and without sensitivity enhancement by TBTDS. For both active nanolayers, the shift of resonance angle is directly proportional to the concentration of Zn2+ in aqueous media. The higher shift of resonance angle was obtained for chitosan–TBTDS active nanolayer due to a specific binding of TBTDS with Zn2+. The chitosan–TBTDS active nanolayer enhanced the sensitivity of detection down to 0.1 mg/l and also induced a selective detection towards Zn2+.